Landscape linguistics in Depok City Village Park - Supriatnoko, Supriatnoko; Mustofa, Anwar; Sinaga, Mawarta Onida; Sugianingsih, Ni Made Widhi (International Journal Labs, 2023)
This research aims to analyse language use in Village Parks Depok City, West Java. The problem raised is the issue of language signs and cultural symbols in Village Parks area of Depok City. This research used a qualitative approach. Data was collected using the observation method through photography techniques. Photos from the photo shoot function as image data. Photos are classified into three taxonomies of sings from Polsky and Cooper (1991), namely information signs, warnings and prohibitions, and warning signs. Data were analysed using a landscape linguistic approach. From the data analysis, the conclusion is obtained: the park is open to the public from 06.00 to 17.00 WIB, the park provided a children’s playground, outdoor gym, and park benches. The language displayed in the park area is in the form of writing, pictures, and writing accompanied by pictures. Writing words, phrases, and sentences complies with Indonesia language rules; the Depok City Government conveyed messages to viators in the form of warnings and prohibitions. Landscape linguistics in Village Parks Depok City tends to use monolingual Indonesian.